Addressing Gaps In Parental Engagement In Learning At Integritas Bangsa Elementary School: A Swot Analysis Approach For Evaluation And Solutions - Ikhlas, Muhammad; Sinaga, Naomi Valentina; Nadzifa, Nazra Haura; Situmorang, Josephine Dwi Inarly; Sirait, Margaretha Tresia; Siregar, Dogom Rizki; Yasmin, Lutfia (Current Issues on Elementary Education Journal, 2025)
This study investigates gaps in parental engagement in learning at Integritas Bangsa Elementary School using SWOT analysis as a tool for evaluation and solution development. Employing a qualitative descriptive approach with a case study design, data were collected through in-depth interviews with homeroom teachers and validated through source triangulation. SWOT analysis was utilized to identify the strengths, weaknesses, opportunities, and threats related to parental participation in education. The findings reveal a nuanced understanding of the dynamics of parental involvement and its impact on students' development. The study proposes actionable solutions, including seminars highlighting the importance of parental engagement, supported by field-based evidence and inspirational stories. Additionally, regular meetings between parents and homeroom teachers are recommended to foster positive relationships and enhance collaboration on children's development. The research underscores the roles of stakeholders: parents are urged to actively participate in their children's education, homeroom teachers to strengthen partnerships with parents, and school principals to facilitate initiatives that improve educational quality. This study provides structured, data-driven recommendations for developing education policies that actively involve parents, aiming to bridge the gap in parental participation and enhance the overall quality of education.